Eficácia e segurança do laser cirúrgico de diodo em incisões circunvestibulares para osteotomia Le Fort I: ensaio clínico randomizado triplo cego - Filipe Jaeger de Oliveira (2017)
The aim of this study was to evaluate through a randomized clinical trial the efficacy and safety of diode laser during the circumvestibular incision for the Le Fort I osteotomy. Patients were randomly allocated in one of three groups based on the technique employed to perform incisions: scalpel, electrocautery or 808nm high-power diode laser. Clinical parameters were used to evaluate the efficacy and safety of the diode laser: incision velocity, duration of the surgery, bleeding, postoperative functions alterations (eating and speech), pain, oedema, wound clinical healing and secondary infection. Thirty patients were enrolled in the study, 10 in each group. The diode surgical laser was effective during cut, but was slower to perform the incisions when compared to conventional techniques (p<0.05). However, no statistically difference was found between the groups in relation to the total surgical time (p>0.05). Regarding bleeding, the incisions performed with diode laser promoted lower bleeding rate in comparison to the scalpel and electrocautery (p=0.00). No statistically significant associations were found between the groups in relation to other clinical parameters studied. In conclusion, the diode laser is effective and safe during the circumvestibular incision for Le Fort I osteotomy.